Contractile actin belt and mesh structures provide the opposite dependence of epithelial stiffness on the spontaneous curvature of constituent cells. (14th July 2017) - Okuda, Satoru; Unoki, Katsuyuki; Eiraku, Mototsugu; Tsubota, Ken‐ichi
Abstract : Actomyosin generates contractile forces within cells, which have a crucial role in determining the macroscopic mechanical properties of epithelial tissues. Importantly, actin cytoskeleton, which propagates actomyosin contractile forces, forms several characteristic structures in a 3D intracellular space, such as a circumferential actin belt lining adherence junctions and an actin mesh beneath the apical membrane. However, little is known about how epithelial mechanical property depends on the intracellular contractile structures. We performed computational simulations using a 3D vertex model, and demonstrated the longitudinal tensile test of an epithelial tube, whose inside and outside are defined as the apical and basal surfaces, respectively. As a result, these subcellular structures provide the contrary dependence of epithelial stiffness and fracture force on the spontaneous curvature of constituent cells; the epithelial stiffness increases with increasing the spontaneous curvature in the case of belt, meanwhile it decreases in the case of mesh. This qualitative difference emerges from the different anisotropic deformability of apical cell surfaces; while belt preserves isotropic apical cell shapes, mesh does not. Moreover, the difference in the anisotropic deformability determines the frequency of cell rearrangements, which in turn effectively decrease the tube stiffness. These results illustrate the importance of the intracellular contractile structures, which may be regulated to optimize mechanical functions of individual epithelial tissues. Abstract : How do cells regulate epithelial mechanics? This study focuses on mechanical roles of contractile actin structures in determining macroscopic mechanics of epithelium. We performed computational simulations of epithelial deformations using the 3D vertex model, and revealed that the contractile belt and mesh structures have the contrary dependence of the epithelial stiffness and fracture force on the spontaneous curvature of constituent cells.